THE EFFECT OF FINANCIAL VARIABLES ON THE COMPANY’S VALUE (Study on Food and Beverage Companies that are listed on Indonesia Stock Exchange Period 2008-2011) - Machfiro, Sonia; Sukoharsono, Eko Ganis (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2012)
This study analyzes and explains the effect of financial variables on the value of Food and Beverage Companies that are listed on Indonesia Stock Exchange period 2008 – 2011. The samples of this research are 11 Food and Beverage Companies that have complete financial reports period 2008-2011. The financial variables used are CR, ROE, EPS, DER, PBV, and ROA and Stock price as representative of company’s value. Based on multiple linear regression analysis, simultaneously, all independent variables significantly affect the stock prices. But partially, only ROE, EPS and PBV that affect stock price of Food and Beverage Companies in the period 2008-2011. The analysis also stated that EPS has the largest beta coefficient value, means the EPS variables have the most dominant influence on stock prices of Food and Beverage Companies in the period 2008-2011 than other financial variable mentioned above. Keywords: Financial Variables, Company’s Value, Food and Beverage Company